Phorbol ester induces elevated oxidative activity and alkalization in a subset of lysosomes - Chen, Chii-Shiarng (BioMed Central, 2002)
BACKGROUND: Lysosomes are acidic organelles that play multiple roles in various cellular oxidative activities such as the oxidative burst during cytotoxic killing. It remains to be determined how lysosomal lumen oxidative activity and pH interact and are regulated. Here, I report the use of fluorescent probes to measure oxidative activity and pH of lysosomes in live macrophages upon treatment with the tumor promotor phorbol 12-myristate 13-acetate (PMA), and provide novel insight regarding the regulation of lysosomal oxidative activity and pH. RESULTS: The substrate used to measure oxidative activity was bovine serum albumin covalently coupled to dihydro-2', 4,5,6,7,7'-hexafluorofluorescein (OxyBURST Green H(2)HFF BSA). During pulse-chase procedures with live macrophages, this reduced dye was internalized via an endocytic pathway and accumulated in the lysosomes. Oxidation of this compound resulted in a dramatic increase of fluorescence intensity. By using low-light level fluorescence microscopy, I determined that phorbol ester treatment results in increased oxidative activity and pH elevation in different subsets of lysosomes. Furthermore, lysosomes with stronger oxidative activity tended to exclude the acidotropic lysosomal indicator, and thus exhibit higher alkalinity. CONCLUSIONS: Results indicate that there is a regulatory mechanism between lysosomal oxidative activity and pH. Activation of lysosomal Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidase by phorbol ester may result in increase of intralysosomal O(2)(•-) and H(2)O(2), concurrent with pH elevation due to consumption of H(+) and generation of OH(-). Furthermore, the effect of phorbol ester on elevated oxidative activity and pH is heterogeneous among total lysosomal population. Higher oxidative activity and/or pH are only observed in subsets of lysosomes.